2010
DOI: 10.1016/j.ajhg.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Distal 7q11.23 Deletion Including HIP1 and YWHAG Identified in Patients with Intellectual Disabilities, Epilepsy, and Neurobehavioral Problems

Abstract: We report 26 individuals from ten unrelated families who exhibit variable expression and/or incomplete penetrance of epilepsy, learning difficulties, intellectual disabilities, and/or neurobehavioral abnormalities as a result of a heterozygous microdeletion distally adjacent to the Williams-Beuren syndrome region on chromosome 7q11.23. In six families with a common recurrent ∼1.2 Mb deletion that includes the Huntingtin-interacting protein 1 (HIP1) and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 51 publications
3
66
0
1
Order By: Relevance
“…In particular, larger WBS deletions extending distally show a more severe developmental delay (DD) or ID phenotype with serious impairments in cognitive function sometimes accompanied by infantile spasms and epilepsy, infrequently diagnosed in WBS patients with common deletion. 10 In this study, we identified two WBS patients with larger deletions towards the telomere. Both patients presented severe DD, ID, and neuropsychological deficits.…”
Section: Patient Wbs166mentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, larger WBS deletions extending distally show a more severe developmental delay (DD) or ID phenotype with serious impairments in cognitive function sometimes accompanied by infantile spasms and epilepsy, infrequently diagnosed in WBS patients with common deletion. 10 In this study, we identified two WBS patients with larger deletions towards the telomere. Both patients presented severe DD, ID, and neuropsychological deficits.…”
Section: Patient Wbs166mentioning
confidence: 96%
“…Among the genes deleted distally to the WBS common deletion interval, HIP1 and YWHAG have been proposed as the most compelling candidate genes for susceptibility to autistic traits, epilepsy, and ID. 10 In a loss-of-function model, mice with targeted mutation in the Hip1 gene developed a neurological phenotype, characterized by failure to thrive, tremor, gait ataxia, and epilepsy. 11 Moreover, Hip1 is crucial for a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptor trafficking in primary hippocampal neurons whose defects are associated with major progressive neurological deficits.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…Three genes-MAGI2 (MIM: 606382), HIP1 (MIM: 601767), and YWHAGhave been suggested as possible candidates for these atypical features. [46][47][48][49][50][51][52][53] Ramocki et al 51 suggested that haploinsufficiency of HIP1 is sufficient to alter neuronal homeostasis and cause focal and generalized epilepsies and cognitive dysfunction. However, their findings do not exclude the possibility that YWHAG loss of function is sufficient to cause neurological phenotypes alone, as proven by our results.…”
mentioning
confidence: 99%
“…Subsequently, in 2010, the deletion of the distal portion (between LCR-C and LCR-D) was identified as a different entity, named distal chromosome 7q11.23 deletion (MIM 613729). The haploinsufficiency of the genes HIP and YWHAG was suggested to be critical for the manifestations of that microdeletion syndrome [Ramocki et al, 2010]. Although 4 patients with a duplication of HIP or HIP / YWHAG were also described by Ramocki et al [2010], which did not comprise the genes between LCR-P and LCR-C, there was no evidence of the relevance of the overexpression of these genes.…”
mentioning
confidence: 84%
“…The haploinsufficiency of the genes HIP and YWHAG was suggested to be critical for the manifestations of that microdeletion syndrome [Ramocki et al, 2010]. Although 4 patients with a duplication of HIP or HIP / YWHAG were also described by Ramocki et al [2010], which did not comprise the genes between LCR-P and LCR-C, there was no evidence of the relevance of the overexpression of these genes. However, Cornell et al [2016] recently provided strong evidence that the duplication of YWHAG causes neuronal migration delay in the developing cerebral cortex of mice, in a similar manner as YWHAG knockdown does.…”
mentioning
confidence: 84%